2014
DOI: 10.5505/tjtes.2014.90868
|View full text |Cite
|
Sign up to set email alerts
|

Are blank cartridge guns really harmless?

Abstract: Blank cartridge guns are devices that discharge sound and gas, but no bullet or shot. These devices are very similar to real guns in the form of their external design and the sound generated during their firing. Although it is widely held in society that these devices are harmless, reports from Turkey and the world have shown that these guns are not entirely innocent. Herein, we present a 26-year-old male with a head injury due to gunshot from a blank cartridge. The purpose of this presentation is to emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, many of publications about blank gun injuries revealed that blank guns could be harmful for the soft tissue and the bone tissue. Our findings were consistent with the literature (1,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In present study, blank guns caused skin tissue damage, destruction of muscle tissue, burnings and the soot, frequently.…”
Section: Discussionsupporting
confidence: 83%
“…Penetrating injury to the head and neck often have lifethreatening features such as airway injury and rupture of major vessels [4][5][6][7]. Gunshot commonly causes serious injury, and although several cases of injuries caused by BCS have been reported, description about features and management of the injuries are insufficient [2,3,8]. The blank cartridge is designated to have the fire sound and gas flare from the gun without the bullet.…”
Section: Discussionmentioning
confidence: 99%
“…The blank cartridge is designated to have the fire sound and gas flare from the gun without the bullet. Its gunpowder and projectile gas could cause injury to human body [2]. Injuries from BCS vary in severity ranging from minor to fatal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the energy created by the blank shot of itself can damage human tissue. [2] When blank shot fired from a gun contacts the head, it can break the skull and damage the brain. [34] When blank shot fired from a gun contacts the chest, it can break the sternum and damage the lungs and heart.…”
mentioning
confidence: 99%